Knowledge of nurses in primary health care about the indication of special coverage (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objective: To identify the knowledge of nurses in primary health care in a municipality about the indication of special coverage. Method: An exploratory, descriptive study with a quantitative approach performed with 101 nurses in 109 health units of primary health care through a structured instrument. The data were statistically analyzed with frequency distribution, percentiles, average, median, standard deviation, coeffi cient of variation, confidence interval, p-value and two-proportion equality test to compare the group that has qualifi cation/improvement in the area with the group do not have. Results: About the indication of the coverage,79.2% reported that it is intended to control exudate and non-viable tissue, and the indication with the highest percentage of correct answers for use in wounds was the silver hydrofi bra coverage and hydrocolloid with silver. Conclusion: Primary care nurses with qualification/improvement courses do not have enough knowledge to indicate the coverage.
Keywords: Nursing; Occlusive healings; Knowledge; Primary health care; Stomatherapy